PEMBERIAN PUPUK ORGANIK CAIR LENGKAP (POCL) Super ACI DENGAN DOSIS BERBEDA TERHADAP PERKEMBANGBIAKAN Moina sp - Rosyadi Rosyadi (UIR Press, 2013)
The aim of this research was to obtain the optimal dose from application of T. petroralis Regan on survival and seeds growth of Spirulina sp. The research was conducted at the hatchery of Faculty of Agriculture Riau Islamic University Pekanbaru during three months. A completely randomized design was used with four treatments, namely P1(5%), P2(10%), P3(15%), P4(20%) per body weight and three replicates. Twenty-days-old seed of T. petroralis Regan were used in this study. The average length and weight of seeds was 1.2 cm and 0.072 g, respectively. The initial stocking density was 5 ind./l. Feed used in this experiment was Spirulina sp (in the form of powder/dry) as a treatment which was obtained from PT. Polaris International Solar Jakarta. The results showed that the highest growth of T. petroralis was found on the treatment of feeding Spirulina sp with dose of 0.625 g of 10%, and the lowest dose of 20%, amounting to 0.452 g. For the growth of fish length Snakeskin Siam, the highest dose was found on Spirulina sp 10% at 1.4 cm, and the lowest dose was 5%, 15% and 20% overall by 1.3 cm. The survival fish of Snakeskin Siamese was at the highest dose of 10% with 88.90% and the lowest dose of 20% was 49.33%, while the daily growth rate of fish weight of Snakeskin Siam obtained from the highest dose of 10% Spirulina sp 7.86%, and the lowest value of 20% at a dose of 6.83%.